Blogs - Siles González, Ignacio (2018)
The Web has been with us now for almost 25 years. An integral part of our social, cultural and political lives, ‘new media’ is simply not that new anymore. Despite the rapidly expanding archives of information at our disposal, and the recent growth of interest in web history as a field of research, the information available to us still far outstrips our understanding of how to interpret it.